2024
DOI: 10.1101/2024.02.08.579387
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sex Differences in Neural Networks Recruited by Frontloaded Binge Alcohol Drinking

Cherish E. Ardinger,
Yueyi Chen,
Adam Kimbrough
et al.

Abstract: Frontloading is an alcohol drinking pattern where intake is skewed toward the onset of access. The goal of the current study was to identify brain regions involved in frontloading. Whole brain imaging was performed in 63 C57Bl/6J (32 female and 31 male) mice that underwent 8 days of binge drinking using the drinking-in-the-dark (DID) model. On days 1-7, three hours into the dark cycle, mice received 20% (v/v) alcohol or water for two hours. Intake was measured in 1-minute bins using volumetric sippers, which f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 48 publications
(103 reference statements)
0
1
0
Order By: Relevance
“…Interestingly, in this study, mice were found to take more fentanyl during the first 30 minutes of the two-hour session than other portions of the session, implying front-loading behavior. Front-loading behavior, which refers to the rapid consumption of a drug at the beginning of a self-administration session, has been more investigated in alcohol drinking (4143). In the present study, the “loading” phase observed within the first 30 minutes may indicate an increased drug intake due to the emergence of negative emotional-like states associated with withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in this study, mice were found to take more fentanyl during the first 30 minutes of the two-hour session than other portions of the session, implying front-loading behavior. Front-loading behavior, which refers to the rapid consumption of a drug at the beginning of a self-administration session, has been more investigated in alcohol drinking (4143). In the present study, the “loading” phase observed within the first 30 minutes may indicate an increased drug intake due to the emergence of negative emotional-like states associated with withdrawal.…”
Section: Discussionmentioning
confidence: 99%